Predictive Factors for Dural Tear in Lumbar Spine Surgery - Abdelaal Abdelbaky (Egyptian Spine Association, 2015)
Background Data: Incidental durotomy is an undesirable but significant complication of lumbar spine surgery Knowing about the predisposing factors for Incidental durotomy and meticulous surgical technique is important to avoid incidental dural tears. Purpose: The purpose of this study is to clarify the risk factors for ID in lumbar spine surgery and to assess the incidence, treatment and outcome of ID. Study Design: Retrospective descriptive clinical case study. Patients and Methods: A retrospective review was conducted on 450 patients who underwent surgical procedure for the treatment of degenerative lumbar spinal disease. Cases included in this study were operated for disc herniation, spinal stenosis, spondylolisthesis and post-laminectomy syndrome. We excluded Patients treated for spinal tumors, trauma, infections and deformity. Results: Incidental durotomies IDs were identified in 27 (6%) patients. The incidence of ID was much higher in revision procedures (11.9%) than in primary spinal procedures (4.6%). 18 (67%) of the 27 tears were caused by residents with the remaining 9 (33%) caused by the attending surgeon. Of the 27 dural tears 11 (40.7%) were caused by the Kerrison rongeur. All dural tears were repaired primarily. All patients achieved satisfactory outcomes other than 2 patients developed pseudomeningocele. Conclusion: Risk factors that can increase the likelihood of ID were older age, obesity, pervious spinal surgery and decreased experience of the surgeon. The most common instrument leading to ID is the Kerrison. Incidental durotomy can be treated successfully with primary watertight repair, subfascial drains and bed rest. (2015ESJ084)